2015
DOI: 10.3727/096504015x14298122915583
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G2/M Arrest by Berberine via Activation of PI3K/Akt and p38 in Human Chondrosarcoma Cell Line

Abstract: Berberine is a clinically important natural isoquinoline alkaloid found in many medicinal herbs. Berberine has been shown to have many pharmacological effects including antimicrobial, antitumor, and anti-inflammatory activities. However, the effects and mechanism of action of berberine have not been studied in chondrosarcoma. Therefore, the effects of berberine on proliferation in a human chondrosarcoma cell line (HTB-94) were investigated. Berberine inhibited cell proliferation in a concentration-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 25 publications
(11 reference statements)
3
33
0
Order By: Relevance
“…In the A-2780 cell line, DMU-214 was shown to decrease the cyclin B1 mRNA level, paralleled to the block in cell cycle progression in the G2/M phase leading to p53-dependent apoptosis. Our results correspond to other authors’ findings showing that cell cycle arrest in the G2/M phase was associated with the inhibition of cyclin B12829. Although we did not find any changes in cyclin B1 expression in SKOV-3, cell cycle arrest in the G2/M phase was observed.…”
Section: Discussionsupporting
confidence: 91%
“…In the A-2780 cell line, DMU-214 was shown to decrease the cyclin B1 mRNA level, paralleled to the block in cell cycle progression in the G2/M phase leading to p53-dependent apoptosis. Our results correspond to other authors’ findings showing that cell cycle arrest in the G2/M phase was associated with the inhibition of cyclin B12829. Although we did not find any changes in cyclin B1 expression in SKOV-3, cell cycle arrest in the G2/M phase was observed.…”
Section: Discussionsupporting
confidence: 91%
“…In our results, we found that cyclin B1 protein was also expressed at lower levels after berberine treatment in BT-20 and HCC70 causing G2/M phase arrest in HCC70. Previous findings report that berberine inhibited the expression of cyclin B1 to induce G2/M phase arrest in numerous cancer types [23,24].…”
Section: Discussionmentioning
confidence: 93%
“…23 In HBT-94 chondrosarcoma cells, BBR upregulated the expression of p53 and p21 by modulating activation of the PI3K/Akt and p38 signaling pathways, which resulted in G2/M phase arrest. 24 In MDA-MB-231 breast cancer cells, BBR arrested cells in S phase, which contributed to high sensitivity of cancer cells to chemotherapy. 25 BBR has also been shown to influence cell cycle through regulation of Rb.…”
Section: Bbr Inhibits Cell Proliferation Bbr Regulates Cell Cyclementioning
confidence: 99%